Parameter‐space‐based robust control of event‐triggered heterogene‐ous platoon - Fangwu Ma; Jiawei Wang; Yang Yu; Liang Wu; Zhenze Liu; Bilin Aksun‐Guvenc; Levent Guvenc (IET Intelligent Transport Systems, 2021)
Abstract A parameter‐space‐based robust platooning controller for the event‐triggered heterogeneous platoon is presented. The novel heterogeneous platoon is established with different longitudinal vehicle dynamic and driving preferences and the event‐triggered communication scheme is designed to reduce the utilization of communication resources. To handle the stricter demand of the heterogeneous system and the disturbance caused by event‐triggered communication scheme, the parameter space approach is adopted to optimize the gains of a robust controller. The feasible region where internal stability and L2 string stability are satisfied is then visualized in the parameters space, by extending the parameter space approach to the D‐stability and frequency response magnitude specifications. Subsequently, the robust controller, which combines the feedforward loop and feedback loop, is developed by selecting the gain from the feasible solution area. The simulation results of the event‐triggered heterogeneous platoon are presented and evaluated to verify the efficiency of this control algorithm. It is seen that the internal stability and string stability of the event‐triggered heterogeneous platoon are guaranteed by this robust controller. Furthermore, 89.7% of communication resources are saved by the application of event‐triggered communication scheme, while the following performance is also favourable during the highway fuel economy cycle.